2014
DOI: 10.1111/all.12463
|View full text |Cite
|
Sign up to set email alerts
|

Medical clowns ease anxiety and pain perceived by children undergoing allergy prick skin tests

Abstract: Medical clowns significantly decrease the level of anxiety perceived by both children undergoing allergy SPT and their parents, as well as the pain perceived by young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 26 publications
3
74
0
6
Order By: Relevance
“…Among the 28 included studies, 18 are randomized prospective and controlled studies and 14 of them have parallels groups design (clowngroup/control-group) [9][10][11][12][13]16,17,[21][22][23][28][29][30]34]. Half of the studies have a sample size of less than 30 patients per group [9,11,13,14,16,18,21,23,29].…”
Section: Methods Evaluation Studies Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the 28 included studies, 18 are randomized prospective and controlled studies and 14 of them have parallels groups design (clowngroup/control-group) [9][10][11][12][13]16,17,[21][22][23][28][29][30]34]. Half of the studies have a sample size of less than 30 patients per group [9,11,13,14,16,18,21,23,29].…”
Section: Methods Evaluation Studies Designmentioning
confidence: 99%
“…One third of the studies targeted specifically the benefits of the intervention of hospital clown for children [17,[19][20][21][22]27,29,30]. Over half of the studies reported intervention benefits of hospital clown for children and their parents [5,[11][12][14][15]18,[23][24][25][26]28,[31][32][33][34]. Four other studies have evaluated in addition the opinions of health professionals [4,10,13,16].…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a clown has been found to reduce the child’s anxiety (Dionigi, Sangiorgi, & Flangini, 2014; Felluga et al, 2016; Goldberg et al, 2014; Kocherov et al, 2016; Meiri, Ankri, Hamad-Saied, Konopnicki, & Pillar, 2016; Messina et al, 2014; Vagnoli, Caprilli, & Messeri, 2010; Vagnoli, Caprilli, Robiglio, & Messeri, 2005; Weintraub et al, 2014) and feelings of boredom, loneliness and sadness (Finlay, Baverstock, & Lenton, 2014; Mansson, Elfving, Petersson, Wahl, & Tunell, 2013; Meiri et al, 2016). Also, a few studies showed that a clown intervention is able to reduce anxiety in parents (Agostini et al, 2014; Fernandes & Arriaga, 2010; Wolyniez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%